Hippocampal alpha7 nicotinic receptors modulate memory reconsolidation of an inhibitory avoidance task in mice - Boccia, Mariano Martin (2010)
CF-1 male mice were trained in an inhibitory avoidance (IA) task using either a mild or a high footshock (0.8 or 1.2 mA, 50 Hz, 1 s). A retention test was given 48 h later. Immediately after the retention test, mice were given intra-dorsal hippocampus infusions of either choline (Ch, an α7 nicotinic acetylcholine receptor (α7nAChR) agonist, 0.08–1.30 μg/hippocampus), or methyllycaconitine (MLA, an α7nAChR antagonist, 1.0–30.0 μg/hippocampus). Memory retention was tested again 24 h later. Methyllycaconitine impaired retention performance regardless of footshock intensity and its effects were long lasting. Ch impaired retention performance only in those mice trained with a high footshock. On the contrary, Ch enhanced retention performance when mice were trained with a mild footshock. These effects were long lasting and dose- and time-dependent. Retention performance was not affected in drug-treated mice that were not subjected to memory reactivation, suggesting that the performance effects could not be attributable to non-specific effects of the drugs. Methyllycaconitine effects were dose-dependently reversed by choline, suggesting that MLA and Ch interact at the α7nAChR. Altogether, results suggest that hippocampal α7nAChRs play a critical role in reconsolidation of an IA response in mice, and may also have important implications for dynamic memory processes. This is the first presentation, to our knowledge, indicating that a specific receptor (α7nAChR) is able to modulate consolidated memories after retrieval.